Visual attention paid to negative comments in cause-related posts: visual style and emotionality matter - Badenes-Rocha, Alberto; Bigne, Enrique; Ruiz-Mafé, Carla (International journal of advertising, 2022)
The goal of this study is to explore how the execution style (product vs. cause) and the emotionality of pictures in brand-generated cause-related marketing (CRM) posts accompanied by negative user comments impact on visual attention. A between-subjects eye-tracking-based experiment was conducted in which 123 participants were exposed to CRM posts published by a fast-food restaurant. The findings showed that the text in CRM posts attracts longer fixation duration than do pictures, although pictures attract attention first. The attention paid to pictures is significantly greater in product-focussed posts, whereas text attracted greater attention in cause-focussed posts. Emotional images received significantly less attention than non-emotional images. Corporate image perceptions and visual attention paid increase customer brand advocacy. We outline theoretical contributions and practical implications for the restaurant sector and make suggestions for future research in the field of CRM persuasion.